Foreign investment and gender equality in India: Competitive pressures or technology transfer? - Jennifer P. Poole; Shruti Sharma (Asian Development Bank Institute (ADBI), 2024)
This paper examines the relationship between foreign direct investment (FDI) inflows into a large, emerging economy and advances in gender equality. Several studies have examined how competitive FDI pressures might lower gender inequality by reducing an employer's ability to practice taste-based discrimination. Other studies examine how FDI-induced technology transfer reduces gender employment and gender wage gaps in developing countries. To the best of our knowledge, we are the first to consider the possibility that foreign investment both places strong competitive pressures on domestic industries and also allows for technology adoption. These ideas are particularly important in service-oriented sectors, where the highest values of foreign investments flow and the largest shares of women are employed. We expect increased competition associated with foreign investment to reduce gender inequality in occupations that suffer most from discrimination, while technology transfer serves to further reduce gender gaps in occupations for which automation reduces the demand for tasks. We use worker-level data from India to examine the differential effects on women relative to men of horizontal (measuring competition) and vertical (measuring technology transfer) FDI across occupational categories. Our findings suggest that competitive pressures associated with horizontal FDI narrow the gender employment gap in nonroutine cognitive occupations, while the technology transfer associated with vertical FDI supports increases in the relative demand for women in routine-manual occupations.
Keywords: F21; F66; J16; J24; 330; foreign direct investment; gender; competition; technology; occupations; tasks